P.207 Reducing the risks of proximal and distal shunt failure in adult hydrocephalus: A Shunt Outcomes Quality Improvement (ShOut-QI) Study. (November 2021) - Hamilton, MG; Ball, C; Holubkov, R; Urbaneja, G; Isaacs, A
Abstract : Background: Ventriculoperitoneal (VP) shunt failures in adult patients are common and subject patients to multiple surgeries and a decreased quality of life. A prospective cohort Shunt Outcomes Quality Improvement (ShOut-QI) initiative was implemented to reduce shunt failure incidence through neuronavigation-assisted proximal catheter insertion and laparoscopy-guided distal catheter anchoring over the liver dome to drain CSF away from the omentum. Methods: "Pre-ShOut" and "Post-ShOut" groups of patients included those with and without neuronavigation/laparoscopy, respectively for insertion of a new VP shunt. The primary outcome was shunt failure which was defined as any return to surgery for shunt revision as determined with a standardized clinical and radiology follow-up protocol. Results: 244 patients (97 Pre-ShOut, 147 Post-ShOut), mean age 73 years, were enrolled over a 7-year interval and observed for a mean duration of 4 years after shunt insertion. Neuronavigation improved proximal catheter placement accuracy by 20% (p<.001), and shunt failure occurred in 57% vs 23% in the Pre-ShOut and Post-ShOut groups, respectively (p=.008), representing a 53% relative risk reduction in the incidence of shunt failure. Conclusions: Adult shunt failure incidence may be significantly reduced by improving the accuracy of proximal catheter placement with neuronavigation and reducing the risk of distal catheter failure with laparoscopic-guided placement.